2013
DOI: 10.1002/ggge.20133
|View full text |Cite
|
Sign up to set email alerts
|

Sulfide geochronology along the Endeavour Segment of the Juan de Fuca Ridge

Abstract: [1] Forty-nine hydrothermal sulfide-sulfate rock samples from the Endeavour Segment of the Juan de Fuca Ridge, northeastern Pacific Ocean, were dated by measuring the decay of 226 Ra (half-life of 1600 years) in hydrothermal barite to provide a history of hydrothermal venting at the site over the past 6000 years. This dating method is effective for samples ranging in age from $200 to 20,000 years old and effectively bridges an age gap between shorter-and longer-lived U-series dating techniques for hydrothermal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(74 citation statements)
references
References 66 publications
2
71
0
Order By: Relevance
“…However, in areas with slower spreading rates, such as the mid-Atlantic Ridge and many backarc spreading systems, vents are spaced farther apart, but are subject to large eruptions less often. Here, age and stability are reflected in the large mineral deposits that have accumulated over many thousands of years (Jamieson et al, 2013). For many vent sites, our observation timeline (only decades) is too short to assess disturbance frequency.…”
Section: Vent Communities As Metacommunitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in areas with slower spreading rates, such as the mid-Atlantic Ridge and many backarc spreading systems, vents are spaced farther apart, but are subject to large eruptions less often. Here, age and stability are reflected in the large mineral deposits that have accumulated over many thousands of years (Jamieson et al, 2013). For many vent sites, our observation timeline (only decades) is too short to assess disturbance frequency.…”
Section: Vent Communities As Metacommunitiesmentioning
confidence: 99%
“…The age of a vent (time since initiation of hydrothermal activity) differs from longevity (duration of most recent hydrothermal activity), since hydrothermal activity may wax and wane over time (Cherkashov et al, 2017). Age tends to be inversely related to spreading rate (Jamieson et al, 2013), ranging from ∼100 years at 13 • N vent field on the fast-spreading EPR (Lalou et al, 1985) to ∼20,000 years at the TAG active field on the slow-spreading MAR (Cherkashov et al, 2017), but less is known about longevity. Hydrothermal systems at volcanic arcs may be active for several thousands of years (e.g., Kermadec arc; de Ronde et al, 2007), whereas others may have decadal spans of activity that are more intimately related to volcanic cycles (Embley et al, 2014).…”
Section: Global Patterns Of Vent Distributions Disturbance Frequencymentioning
confidence: 99%
“…7). Jamieson et al (2013) pointed out that this slight anticorrelation may reflect the amount of time a section of ocean curst resides within the hydrothermally active neovolcanic zone of a spreading center.…”
Section: Episodes Of Hydrothermal Activitymentioning
confidence: 99%
“…When applying the 230 Th/ 238 U dating method, two assumptions are made: the negligible initial 230 Th and closed system decay after mineral formation (Lalou et al 1985(Lalou et al , 1986. Other U-Th disequilibrium methods such as 226 Ra/ 210 Pb,228 Ra/ 228 Th and 210 Pb/Pb were used to determine the age of deposits\150 years (Lalou et al 1986;Jamieson et al 2013). While the ESR (electron spin resonance) dating of barite ( 226 Ra/ 228 Ra) in seafloor hydrothermal fields can obtain ages of 300-3620 years (Kasuya et al 1991;Okumura et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Jamieson et al 2013, and references therein). Such a small amount of constraint is partly attributable to the limited availabilities of numerical dating methods applied to the hydrothermal deposits at inactive sites directly: a gap of 10 2 -10 3 years (Jamieson et al 2013). One early trial of geochronology is reported by Lalou et al (1985).…”
Section: Introductionmentioning
confidence: 99%